First evidence of bubble-net feeding and the formation of ‘super-groups’ by the east Australian population of humpback whales during their southward migration - Pirotta, Vanessa; Owen, Kylie; Donnelly, David; Brasier, Madeleine J.; Harcourt, Robert (Aquatic Conservation: Marine and Freshwater Ecosystems, 2021)
1. The recovery of overexploited populations is likely to reveal behaviours that may have been present prior to harvest but are only now reappearing as the population size increases. The east Australian humpback whale ( Megaptera novaeangliae ) population (group V, stock E1) has recovered well from past exploitation and is now estimated to be close to the pre-whaling population size. 2. Humpback whales were thought to follow a ‘feast and famine’ model historically, feeding intensively in high-latitude feeding grounds and then fasting while migrating and in calving grounds; however, there is growing evidence that animals may feed outside of known foraging grounds. 3. This short article reports on the first photographically documented evidence of bubble-net feeding by humpback whales in Australian coastal waters (n = 10 groups observed) and provides the first evidence of a second site in the southern hemisphere for the formation of ‘super-groups’ (n = 6 super-groups at discrete locations). 4. The formation of super-groups may be linked to changes in the type or density of prey available, either along the migratory route or in the feeding grounds of the previous summer. It is also possible that the increased population size following recovery make large group sizes while feeding more common. These findings strongly support evidence that feeding behaviour is not restricted to high-latitude foraging grounds in the Southern Ocean, and that prey consumption prior to leaving the coastal waters of Australia may be a significant component of the migratory ecology of this population. 5. Understanding how environmental variation influences the extent to which humpback whales depend on foraging opportunities along their migratory route, and where feeding occurs, will help to predict how future changes in the ocean will influence whale populations. This will also allow for more effective management measures to reduce the impact of threats during this important period of energy consumption.